The Use of Artificial Intelligence (AI) in Writing a Thesis by EFL Postgraduate Students - Asmawati; Utami Dewi; Sholihatul Hamidah Daulay (Universitas Islam Negeri Palopo, 2025)
This research explores the use of Artificial Intelligence (AI) in thesis writing by four postgraduate students who are English as a Foreign Language (EFL) learners at an Indonesian university. Employing a qualitative phenomenological approach, data were collected over a two-month period through open-ended questionnaires, in-depth interviews, and documentation analysis. The findings reveal that students utilized various AI tools such as Grammarly, QuillBot, ChatGPT, Claude, Meta AI, and Perplexity, across different stages of their writing process, including brainstorming, paraphrasing, grammar correction, structural organization, and language refinement. Before adopting AI, participants encountered challenges in idea development, coherence, and linguistic accuracy. Following the integration of AI tools, they reported improvements in clarity, organization, and writing confidence. Most students expressed a strong willingness to continue using AI due to its perceived benefits in enhancing efficiency, precision, and learning outcomes. While limited to one university context in Indonesia, this study provides insights into the positive role of AI integration in supporting academic writing development among EFL postgraduate students.